2020
DOI: 10.1186/s12885-020-07520-x
|View full text |Cite
|
Sign up to set email alerts
|

Seeking healthcare at their ‘right’ time; the iterative decision process for women with breast cancer

Abstract: Background About 85% of breast cancer patients attending Komfo Anokye Teaching Hospital (KATH), Ghana, present with stage III/IV disease. In spite of great investments into the early diagnosis and management of breast cancer, late presentation persists and poses a barrier to realising the possible benefits of the gains made in breast cancer management. This study assessed the symptom appraisal and medical health seeking behaviour of women with either locally advanced or metastatic breast cancer attending breas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Two studies described women's symptom recognition, appraisal and intent to seek medical care, whereas the third described the diagnosis and treatment procedures. 4 , 7 , 8 However, no study has outlined in detail the pathways that women in Ghana navigate from symptom detection through treatment receipt. Understanding this full process and appreciating women's understanding and needs is essential if effective interventions are to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies described women's symptom recognition, appraisal and intent to seek medical care, whereas the third described the diagnosis and treatment procedures. 4 , 7 , 8 However, no study has outlined in detail the pathways that women in Ghana navigate from symptom detection through treatment receipt. Understanding this full process and appreciating women's understanding and needs is essential if effective interventions are to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies23 28–30 demonstrated that high cost of medical treatment led to use of herbal and traditional alternatives. Prioritisation of finances on family led to delays in accepting treatment 23 24 31. Financial barriers impacted negotiation of care31; those from a lower income were more likely to experience longer wait times 32…”
Section: Resultsmentioning
confidence: 99%
“…Prioritisation of finances on family led to delays in accepting treatment. 23 24 31 Financial barriers impacted negotiation of care 31 ; those from a lower income were more likely to experience longer wait times. 32 Fears and beliefs about treatment and its outcomes Obrist et al 33 found patients who believed in the efficacy of treatment were more likely to complete treatment in single variable analysis, although this was not significant in multivariate models where potential confounding factors were controlled for.…”
Section: Financial Barriersmentioning
confidence: 99%
“…Symptom interpretation is the most important step in seeking medical help and is believed to encourage up to 80% of women in seeking medical help. 23 Women cannot, however, be expected to know which symptoms they should act on and present to any healthcare system in the absence of co-ordinated awareness programmes driven by that system. These programmes need to be based on women’s experiences of a breast cancer symptoms and diagnosis and to be developed and evaluated for acceptability in collaboration with women from the relevant communities.…”
Section: Discussionmentioning
confidence: 99%